ANALISIS KEBUTUHAN PENGEMBANGAN E-LKPD BERBASIS ECOPRENEURSHIP PADA TOPIK ENERGI TERBARUKAN UNTUK MENINGKATKAN PERILAKU PEDULI LINGKUNGAN SISWA SMA - Sakti, M Teja; Emiliannur, Emiliannur (Universitas Negeri Malang, 2024)
Environmental problems are increasingly urgent to be addressed, considering their broad impact on ecosystems and human life. Environmentally friendly behavior that is not instilled from an early age will cause more environmental problems. One group that has a strategic role in environmental problems is students. Students often show ignorance towards the environment, which is reflected in their behavior of throwing rubbish carelessly in the school environment. One of the reasons is that teaching materials do not direct students to pay attention to the fact that there is waste that can be processed and has economic value while also overcoming environmental problems. Teaching materials that support this problem are Ecopreneurship-based E-LKPD. The type of research used is development research with a plomp model that uses preliminary analysis. This research aims to describe the results of analyzing the needs for developing ecopreneurship-based digital teaching materials. The subjects of this research were two physics teachers and 64 students of SMAN 1 Candung. Data was collected using a questionnaire and analyzed to conclude. The conclusions of this research indicate that 1) digital materials have not been used for learning, and 2) there is a need to develop ecopreneurship-based teaching materials to support student project assignments.